Core competencies for patient safety research: a cornerstone for global capacity strengthening. Issue 1 (12th January 2011) - Andermann, Anne; Ginsburg, Liane; Norton, Peter; Arora, Narendra; Bates, David; Wu, Albert; Larizgoitia, Itziar; ,
Abstract : Background: Tens of millions of patients worldwide suffer disabling injuries or death every year due to unsafe medical care. Nonetheless, there is a scarcity of research evidence on how to tackle this global health priority. The shortage of trained researchers is a major limitation, particularly in developing and transitional countries. Objectives: As a first step to strengthen capacity in this area, the authors developed a set of internationally agreed core competencies for patient safety research worldwide. Methods: A multistage process involved developing an initial framework, reviewing the existing literature relating to competencies in patient safety research, conducting a series of consultations with potential end users and international experts in the field from over 35 countries and finally convening a global consensus conference. Results: An initial draft list of competencies was grouped into three themes: patient safety, research methods and knowledge translation. The competencies were considered by the WHO Patient Safety task force, by potential end users in developing and transitional countries and by international experts in the field to be relevant, comprehensive, clear, easily adaptable to local contexts and useful for training patient safety researchers internationally. Conclusions: Reducing patient harm worldwide will require long-term sustained efforts to build capacity to enable practical research that addresses local problems and improves patient safety. The first edition of Competencies for Patient Safety Researchers is proposed by WHO Patient Safety as a foundation for strengthening research capacity by guiding the development of training programmes for researchers in the area of patient safety, particularly in developing and transitional countries, where such research is urgently needed.